2020
DOI: 10.1038/s41598-020-61604-z
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of Clostridiodes diffiicle PCR ribotypes 001 and 126 in Iran

Abstract: Clostridium difficile is a leading causative agent of hospital-acquired and community-acquired diarrhea in human. This study aims to characterize the predominant C. difficile strains, RT001 and 126, circulating in Iranian hospitals in relation to resistant phenotypes, the antibiotic resistance genes, and their genetic relatedness. A total number of 735 faecal specimens were collected from patients suspected of CDI in Tehran hospitals. Typing and subtyping of the strains were performed using CE-PCR ribotyping a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…The bacterial infection was induced except in the vehicle control group. An intramuscular (IM) injection (10 µL) of the bacterial suspension, equivalent to 0.2 (~1 × 10 6 . CFU/mL) was administered to each fish.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bacterial infection was induced except in the vehicle control group. An intramuscular (IM) injection (10 µL) of the bacterial suspension, equivalent to 0.2 (~1 × 10 6 . CFU/mL) was administered to each fish.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, in an environmental study done by Walsh et al, 5 samples from sewage and drinking water comprised different bacterial strains concealing enzymes responsible for resistance for most of the beta‐lactam antibiotics, suggesting a transfer between the species. Baghani et al 6 reported a high occurrence of different ribotypes of Clostridioides difficile , in which most were multidrug resistant.…”
Section: Introductionmentioning
confidence: 99%
“…The result of the culture method showed the 20.0% (n = 10/50) frequency rate for C. difficile . Using culture method, in previous studies by Shoaei et al ( 2019 ) from Isfahan, Iran and Baghani et al ( 2020 ) from Tehran, Iran, a higher (28.6%) and a lower (8.8%) frequency rate was reported for C. difficile , respectively. Also, Putsathit et al ( 2017 ) from Thailand and Plants-Paris et al ( 2019 ) from Kenya reported the C. difficile strains in 23.7% (n = 100/422) and 37.6% of the stool samples using the direct culture method.…”
Section: Discussionmentioning
confidence: 92%
“…In our previous study that used a large collection of C. di cile isolates, RT 001 (12.9%), RT 126 (11.2%), and RT 084 (3.3%) were the most frequent RTs identi ed in CDI patients across different hospitals and medical centers in Tehran [39]. In a recent study by Baghani et al, RT 001 (32.3%) and RT 126 (9.2%) were also reported as the most common RTs isolated from patients with CDI in Tehran [40]. To date, RT 027 isolates have not been reported from Iranian patients.…”
Section: Discussionmentioning
confidence: 93%